2015
DOI: 10.15604/ejss.2015.03.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chinese FDI on Employment Generation in the Building and Construction Sector of Ghana

Abstract: One of the major concerns of governments in Africa in general and Ghana in particular is unemployment and underemployment. Most developing countries especially African countries compete to attract foreign direct investment (FDI) into their economies with the desire of improving employment level and securing a sustainable development leading to economic growth. In view of this, the creation of jobs for the unemployed and technology transfer through Chinese investments has become complementary since Chinese FDI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…These results are like those obtained under the income inequality function (see results in Table 6). They generally mean that FDI reduced poverty, which is consistent with Boakye-Gyasi and Li's (2015) theoretical rationale that FDI enables people to get skills, enhances human capital development, and creates employment and wealth, thereby reducing poverty and narrowing the income inequality gap.…”
Section: Panel Co-integration Testssupporting
confidence: 65%
“…These results are like those obtained under the income inequality function (see results in Table 6). They generally mean that FDI reduced poverty, which is consistent with Boakye-Gyasi and Li's (2015) theoretical rationale that FDI enables people to get skills, enhances human capital development, and creates employment and wealth, thereby reducing poverty and narrowing the income inequality gap.…”
Section: Panel Co-integration Testssupporting
confidence: 65%
“…Similarly, Boakye-Gyasi and Li (2015) focussed on the contribution of China’s FDI to employment generation in the building and construction sector of Ghana. By using a robust regression model, they found that Chinese FDI flows affect employment through direct effects on building and construction sector of Ghana.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Tang (2016), Lam (2014), Corkin (2012) have also discover that the longer Chinese companies operate in Africa, the more they rely on local workers. Using a formal robust regression estimation, Boakye-Gyasi and Li (2015) suggest that there is a positive and significant impact of inward Chinese FDI flows on employment in Ghana via a direct effect on Ghana's building and construction sector. Oya and Schaefer (2019), based on interviews of 1,500 Angolan and Ethiopian workers, further demonstrate that Chinese firms pay local workers comparable wages and train them to similar standards as non-Chinese foreign firms in Africa, although usually less formally.…”
Section: Discussion Of Our Findings So Farmentioning
confidence: 99%